2019
DOI: 10.3389/fimmu.2019.00442
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Coinfection Attenuates Murine Toxoplasma gondii-Induced Crohn's-Like Ileitis by Preserving the Epithelial Barrier and Downregulating the Inflammatory Response

Abstract: Background and aims: Mice orally infected with T. gondii develop Crohn's disease (CD)-like enteritis associated with severe mucosal damage and a systemic inflammatory response, resulting in high morbidity and mortality. Previously, helminthic infections have shown therapeutic potential in experimental colitis. However, the role of S. mansoni in T. gondii-induced CD-like enteritis has not been elucidated. Our study investigated the mechanisms underlying T. gondii-induced ileitis and the potential therapeutic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…As it was previously demonstrated that larval S stercoralis soluble extract itself has the capacity to recruit neutrophils in vivo, 85 we investigated the MPO, an indicative of neutrophil activity in the ileum of infected and SvAg‐treated mice. The SvAg treatment alone was not able to alter the MPO activity in the ileum; however, in accordance with previous studies, 82 T gondii infection increased MPO activity in SvAg‐treated mice. The neutrophils present important mechanisms that are involved in the control of T gondii , such as cytokine and reactive oxygen species (ROS) production, and formation of neutrophil extracellular traps (NETs) (reviewed in 86) 86 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As it was previously demonstrated that larval S stercoralis soluble extract itself has the capacity to recruit neutrophils in vivo, 85 we investigated the MPO, an indicative of neutrophil activity in the ileum of infected and SvAg‐treated mice. The SvAg treatment alone was not able to alter the MPO activity in the ileum; however, in accordance with previous studies, 82 T gondii infection increased MPO activity in SvAg‐treated mice. The neutrophils present important mechanisms that are involved in the control of T gondii , such as cytokine and reactive oxygen species (ROS) production, and formation of neutrophil extracellular traps (NETs) (reviewed in 86) 86 .…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it was verified if the SvAg treatment could improve the inflammatory alterations induced by the parasite. Previous studies demonstrated that experimental T gondii infection reduces goblet numbers 81,82 and eliminates Paneth cells 83,84 in the small intestine. As expected, in the present investigation T gondii infection induced inflammatory lesions in the small intestine, lung and liver of infected mice and reduced intestinal Paneth and goblet cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that helminth-derived compounds induced a Th1/Th2 switch that ameliorated experimental colitis 52 , 53 . Other studies reported that the coinfection with S. mansoni attenuated Crohn’s like inflammatory bowel disease, preserving the epithelial barrier function by downregulating the inflammatory response 54 . In a recently published study, the therapeutic effect of autoclaved S. mansoni antigens on toxin induced colon cancer was demonstrated in a murine model 55 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, considering the Balb/c I and XID I groups, a reduction in the number of Paneth cells occurred, perhaps due to increased degranulation [48][49][50] after infectious conditions. 32,51,52 As previously described, VL causes several intestinal changes, 10,11,38 since the parasite leads to disruption of the intestinal homeostasis. 7,8,12 It can happen due to the presence of the parasite in the organ or as a systemic reaction and could be related to the B-1 cells.…”
Section: Discussionmentioning
confidence: 88%
“…This cytokine contributes to the Paneth cells development, as observed by the increased number of these cells after the adoption of B‐1 cells that resembled those found in the infected wild group. On the other hand, considering the Balb/c I and XID I groups, a reduction in the number of Paneth cells occurred, perhaps due to increased degranulation after infectious conditions …”
Section: Discussionmentioning
confidence: 96%